Pengembangan Media Audio Visual Layanan Klasikal Bidang Karir pada Materi Orientasi Masa Depan di SMA Srijaya Negara Palembang - Islamiati, Tri Septiana; Sofah, Rahmi; Harlina, Harlina (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2019)
This type of research is development research by using the ADDIE model. This research aimed to produce products of audio visual media which were valid, practical and effective. The research was conducted at SMA Srijaya Negara Palembang. This research consisted of 5 stages, namely 1) analysis (pre-test and interview with BK teacher), 2) design (making RPL and media manuscript), 3) development (making media, after the media was finished, the researcher conducted validation with three experts: material expert, media expert, language expert and small group test), 4) implementation (field test and post-test), 5) evaluation (strengths and limitations of the media). The results obtained at pretest with materials that can be updated in the future are 47.9% in the "moderate" category, which means that students still need improvement. From the comments and suggestions given by the three experts, the results of themedia were valid and appropriate to be tested in a small group trial. The students gave comments and suggestions to improve the video, after which the researcher conducted a field test, the results obtained were 87% "very practical" and in the post-test 88.9% of the" high "category wasobtained. The effectiveness of audio visual media obtained by N-Gain was 0.71 which "high" category. From the results of the research, it can be concluded that the classical audio visual service media developed has been valid, practical and effective used in classical service delivery on the career field of future orientation materials.